W-algebras as coset vertex algebras - Arakawa, Tomoyuki; Creutzig, Thomas; Linshaw, Andrew R. (Inventiones Mathematicae, 2019)
We prove the long-standing conjecture on the coset construction of the minimal series principal W-algebras of ADE types in full generality. We do this by first establishing Feigin’s conjecture on the coset realization of the universal principal W-algebras, which are not necessarily simple. As consequences, the unitarity of the “discrete series” of principal W-algebras is established, a second coset realization of rational and unitary W-algebras of type A and D are given and the rationality of Kazama–Suzuki coset vertex superalgebras is derived.
CRIS-Team Scopus Importer:2024-06-24